Effect of lactation induction on milk production and composition, oxidative and antioxidant status, and biochemical variables. (May 2016) - Radavelli, Willian; Campigotto, Gabriela; Machado, Gustavo; Bottari, Nathieli; Bochi, Guilherme; Moresco, Rafael; Morsch, Vera; Schetinger, Maria; Bianchi, Anderson; Baldissera, Matheus; Ferreira, Rogério; da Silva, Aleksandro
Abstract This study aimed to induce lactation in Lacaune sheep and to verify its influence on milk production and composition, oxidative/antioxidant profile, and biochemical variables in serum and milk. A group of ewes (group A, n = 7) was induced with estradiol (0.5 mg/kg body weight (BW)) and progesterone (1.25 mg/kg BW) on days 1 to 7, bovine somatotropin (BST; 250 mg/animal) on days 11 and 40, as well as dexamethasone (16 mg/day) on days 19, 20, and 21. For comparison, another group of pregnant ewes was used as control (group B, n = 5). Blood and milk samples were collected for biochemical analysis, oxidative/antioxidant profile analysis, and determination of individual volume and chemical composition. The hormonal protocol was effective to induce lactation; however, milk production was 79 % lower than the control group. Milk fat, protein, and total solids were significantly lower (p < 0.05) in group A when compared to group B. Hormonal induction caused changes in blood components such as increased amounts of albumin, ALT, and gamma-glutamyl transferase (GGT) and decreased urea compared to the control group. Seric antioxidant levels (ferric reducing ability of plasma (FRAP), group A) were significantly increased, and reactive species of oxygen decreased dramatically compared to group B. Milk FRAP levels were lower in group A, and advanced oxidation protein product (AOPP) levels were higher compared to group B. Therefore, it was concluded that the protocol for lactation induction of Lacaune ewes was not effective in the biochemical change in blood and milk.